SPATIOTEMPORAL VISIBILITY CHARACTERISTICS IMPACTED BY FOREST AND LAND FIRE OVER AIRPORTS IN SUMATERA AND BORNEO ISLAND, INDONESIA - Ismanto, Heri; Hartono, Hartono; Marfai, Muh Aris (Quaestiones Geographicae, 2019)
Smoke can reduce the airport’s visibility and is related to the aviation safety and efficiency. Low visibility has potential safety hazard, such GA-152 crashed in 1997, and thus there is a need to find out the visibility characteristics in airports over Sumatra and Borneo Island caused by 2015 forest fire. This research aims to analyse the spatiotemporal visibility characteristics over airports in Sumatera and Borneo Island using flight rule visibility below minima criteria and hazard probability. The analysis of smoke was characterized using visibility severity index (VSI) that is a function of visibility severity class and its probability level. Spatiotemporal analysis of severity index combined with hotspot and wind numerical weather model indicates that the worst impact visibility occurred in September and October 2015. The lowest visibility was occured over night until afternoon time period. The spread of VSI impact has a tendency to northward and northwestward. The very high VSI levels occurred at airports such: WIJJ (Jambi), WIBB (Pekanbaru), WAGG (Palangkaraya) which were impacted up to 70% of flight operations time with IFR visibility below minima; while the WIOS (Susilo-Sintang), which operates only on VFR, experienced about 92% of VFR visibility below minima at smoke climax period.